2019
DOI: 10.1002/ecy.2888
|View full text |Cite
|
Sign up to set email alerts
|

Species energy and Thermal Performance Theory predict 20‐yr changes in ant community abundance and richness

Abstract: In an era of rapid climate change, and with it concern over insect declines, we used two theories to predict 20-yr changes in 34 North American ant communities. The ecosystems, from deserts to hardwood forests, were first surveyed in the 1990s. When resurveyed in 2016-2017, they averaged 1°C warmer with 200 g CÁm À2 Áyr À1 higher plant productivity. Ant colony abundance changed from À49% to +61%. Consistent with Thermal Performance Theory, colony abundance increased with temperature increases < 1°C, then decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…A decelerating benefit of temperature in locations with greater increases in temperature is consistent with previous long-term studies of insects. In a study of two surveys of ant communities across North America conducted 20 years apart, and finding that sites with the largest increases in temperature had the largest declines in colony density (Kaspari et al, 2019). Hallmann et al (2017) found a positive effect of temperature on insect biomass; however, biomass loss over time was greatest in mid-summer, when temperatures are highest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A decelerating benefit of temperature in locations with greater increases in temperature is consistent with previous long-term studies of insects. In a study of two surveys of ant communities across North America conducted 20 years apart, and finding that sites with the largest increases in temperature had the largest declines in colony density (Kaspari et al, 2019). Hallmann et al (2017) found a positive effect of temperature on insect biomass; however, biomass loss over time was greatest in mid-summer, when temperatures are highest.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of climate change are geographically pervasive (Wilson and Fox 2020) and may explain insect decline in natural areas (Rada et al 2019, Janzen and Hallwachs 2019, Baranov et al 2020, Welti et al 2020a. Some insect taxa are currently benefiting from rising temperatures, which can increase local populations (Kaspari et al 2019, Baker et al 2021), diversity (Hofmann et al 2018), and species' range sizes (Termaat et al 2019). However, as temperatures continue to rise and increase more rapidly, temperature is expected to decrease insect productivity (Warren et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016–2017, ants were resampled from May to August across North America at 33 sites previously sampled in 1994–1997 (Fig. 1; Kaspari et al 2000, Kaspari et al 2019). These sites spanned 15.7° in latitude and 51.6° in longitude from warm southwestern deserts in California to cool northeastern deciduous forests in Massachusetts.…”
Section: Methodsmentioning
confidence: 99%